The Big Bang Theory: Roles and contributions of Middle Managers in Cypriot Banking Industry’s Strategic Reconstruction - Galanis, Renos (2013)
Purpose Middle managers are the organizational actors burdened with the task to implement changes that others –senior management most likely– have designed. The dichotomy in literature regarding their contribution to strategic change is evident. Some authors strongly defend their importance in strategic change management whilst others label them as obstructive, resisters and saboteurs.